Joint parental care - Yakuppur, Sendi (Pravnik, 2015)
There are many legal arrangements under the Turkish Civil Code regarding parental care. According to this regulation legislator explicitly accepts joint parental care as a general rule during the marriage. This rule is applied also for the case when married couple lives separated from one another. Notwithstanding, under Turkish Civil Code there is no explicit legal arrangement about joint parental care in case when parents are not married and in case they are divorced. This fact causes hesitations about determining whether judge is authorized to rule for joint parental care in these two circumstances. According to the general opinion, it cannot be concluded that joint parental care is explicitly excluded under all circumstances. However, it is very difficult to determine under which conditions judge shall rule for joint parental care. Therefore special arrangement needs to be done. The new arrangement should not regulate the joint parental care as a rule but it should empower the judge to rule for joint parental care only in the presence of specific conditions.
Keywords: child; družinsko pravo; otroci; starši; Turčija; Turkey